PENGEMBANGAN E-BOOKLET JENIS-JENIS JAMUR MAKROSKOPIS DI TEPIAN SUNGAI DESA MAWANGI SEBAGAI BAHAN AJAR TAMBAHAN MATERI JAMUR - Zuhrah, Siti Nadzifah; Amintarti, Sri (BIOEDUKASI (Jurnal Pendidikan Biologi), 2026)
The lack of digital-based teaching materials and local potential on macroscopic fungi material that is considered difficult to understand by students can be developed into e-booklet teaching materials. This study aims to describe the suitability, feasibility, readability and effectiveness of e-booklets on types of fungi on the banks of the Mawangi village river. This study uses the 4D development model (Define, Design, Develop, and Disseminate) and is limited to the limited disseminate stage. The suitability and feasibility test was carried out by 3 experts, the readability test by 9 students, and the effectiveness test by 17 students. The results of the suitability test obtained an average score of 4.22 (very suitable), the feasibility test obtained an average score of 4.33 (very feasible), the readability test of students obtained an average of 4.71 (very good) and the results of the effectiveness test of students obtained an average score of 0.61 (moderate). Based on these results, it shows that this e-booklet is suitable for use as additional teaching materials on the material on the biodiversity of the mushroom sub-concept.Kata kunci: 4D, desa Mawangi, e-booklet, jamur makroskopis